The Effect Of Service Quality and The Mediating Role Of Costumer Satisfaction Towards Service Loyalty in Boxins Industry Study Case : Casa Boxe - Pramura, Rayendra Abiyasa; Fachira, Ira (Journal of Business and Management, 2016)
Abstract Six months since its opening, Casa Boxe only has 155 customers with only 20% of them are taking membership program. In previous studies, customer satisfaction is a key factor in influencing the loyalty of a customer. The research was done with collecting questionnaire from 71 customers of Casa Boxe to analyze the current level Of service quality, Customer Satisfaction and Service Loyalty. The result indicate that, the current level of Casa Boxe’s service qualiy can be categorized as good and with the lowest score on Reliability sub-dimensions. While for the level of Casa Boxe’s customer satisfaction and service loyalty is high. Findings also show that empathy and tangible dimensions significantly influence customer satisfaction, leading to service loyalty.Keywords: Service Loyalty, Service Quality, Customer Satisfaction